Theoretical Analysis of Algorithmic Competence as an Object of Pedagogical Analysis - Axmedova, Nilufar (International Journal on Orange Technologies, 2022)
In this study, the algorithmic competence of students is theoretically analyzed as an object of pedagogical analysis.